AKTIVITAS INHIBISI ENZIM ALFA-GLUKOSIDASE EKSTRAK DAUN JOMBANG (TARAXACUM OFFICINALE) SECARA IN VITRO - Nuhaa Zuhdiyyah (2023)
Type 2 diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia due to insulin resistance. One of the therapies for lowering blood sugar levels is using drugs that inhibit the alpha-glucosidase enzyme. The alpha-glucosidase enzyme plays a role in the hydrolysis of carbohydrates into glucose in the intestine. Jombang leaves are a plant material that has the potential to be an antidiabetic. This research was an experimental study with samples of jombang leaf extract in 50% and 96% ethanol solvents. Alpha-glucosidase enzyme inhibition activity was tested in vitro using the colorimetric method. Jombang leaf extract with 50% ethanol solvent showed better alpha-glucosidase enzyme inhibition activity (IC50 25.399 ppm) compared to 96% ethanol solvent (IC50 319.107 ppm). The difference in the percentage inhibition of the alpha-glucosidase enzyme from the use of the two solvents showed no significant difference (Sig.>0,05).